Route of Glucose Uptake in the Group a Streptococcus Impacts SLS-Mediated Hemolysis and Survival in Human Blood - Sundar, Ganesh S.; Islam, Emrul; Braza, Rezia D.; Silver, Aliyah B.; Le Breton, Yoann; McIver, Kevin S. (Frontiers in Cellular and Infection Microbiology, 2018)
The transport and metabolism of glucose has been shown to have far reaching consequences in the transcriptional profile of many bacteria. As glucose is most often the preferred carbon source for bacteria, its presence in the environment leads to the repression of many alternate carbohydrate pathways, a condition known as carbon catabolite repression (CCR). Additionally, the expression of many virulence factors is also dependent on the presence of glucose. Despite its importance, little is known about the transport routes of glucose in the human pathogen Streptococcus pyogenes. Considering that Streptococcus pyogenes is an important human pathogen responsible for over 500,000 deaths every year, we characterized the routes of glucose transport in an effort to understand its importance in GAS pathogenesis. Using a deletion of glucokinase (∆nagC) to block utilization of glucose imported by non-PTS pathways, we determined that of the two glucose transport pathways in GAS (PTS and non-PTS), the non-PTS pathway played a more significant role in glucose transport. However, the expression of both pathways is linked by a currently unknown mechanism, as blocking the non-PTS uptake of glucose reduces ptsI (EI) expression. Similar to the effects of the deletion of the PTS pathway, lack of the non-PTS pathway also leads to the early activity of Streptolysin S. However, this early activity did not adversely or favorably affect survival of ∆nagC in whole human blood. In a subcutaneous murine infection model, ∆nagC-infected mice showed increased lesion severity at the local sight of infection; although, lesion size and dissemination from the site of infection was similar to wild type. Here, we show that glucose transport in GAS is primarily via a non-PTS pathway. The route of glucose transport differentially affects the survival of GAS in whole human blood, as well as the lesion size at the local site of infection in a murine skin infection model.